Handbook of Evolutionary Research in Archaeology - Prentiss, Anna Marie (Springer International Publishing : Imprint: Springer, 2019)
Evolutionary Research in Archaeology seeks to provide a comprehensive overview of contemporary evolutionary research in archaeology. The book will provide a single source for introduction and overview of basic and advanced evolutionary concepts and research programs in archaeology. Content will be organized around four areas of critical research including microevolutionary and macroevolutionary process, human ecology studies (evolutionary ecology, demography, and niche construction), and evolutionary cognitive archaeology. Given a focus on theory and application the book does not seek comprehensive coverage of the full range of empirical work as measured temporally and geographically. Authors of individual chapters will address theoretical foundations, history of research, contemporary contributions and debates, and implications for the future for their respective topics. As appropriate and within space limits authors could present or discuss short empirical case studies to illustrate key arguments.